2015
DOI: 10.3345/kjp.2015.58.11.440
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics and causes of chest pain in children and adolescents

Abstract: PurposeChest pain is common in children and adolescents and is a reason for referral to pediatric cardiologists. Although most cases of chest pain in these age groups are benign and do not require treatment, timely diagnosis is important not to miss life-threatening diseases requiring prompt treatment. We investigated certain clinical characteristics that may be useful in the diagnosis of such critical diseases.MethodsPatient medical records between July 2006 and September 2013 were retrospectively examined. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
1
17
1
2
Order By: Relevance
“…1,2 The most common causes of chest pain in children are non-cardiac and include musculoskeletal and idiopathic origins, and cardiac diseases are found in the aetiology of chest pain in a small portion of the cases ranging from less than 1 to 10%. [3][4][5][6] Careful evaluation of medical history, and physical examination should be performed due to high mortality of cardiac-related chest pain in cases without rapid diagnosis and treatment. 3,5,7 However, there is a controversy about determining which child could be affected by a serious organic disease and which tests could be performed for an exact diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The most common causes of chest pain in children are non-cardiac and include musculoskeletal and idiopathic origins, and cardiac diseases are found in the aetiology of chest pain in a small portion of the cases ranging from less than 1 to 10%. [3][4][5][6] Careful evaluation of medical history, and physical examination should be performed due to high mortality of cardiac-related chest pain in cases without rapid diagnosis and treatment. 3,5,7 However, there is a controversy about determining which child could be affected by a serious organic disease and which tests could be performed for an exact diagnosis.…”
mentioning
confidence: 99%
“…[3][4][5][6] Careful evaluation of medical history, and physical examination should be performed due to high mortality of cardiac-related chest pain in cases without rapid diagnosis and treatment. 3,5,7 However, there is a controversy about determining which child could be affected by a serious organic disease and which tests could be performed for an exact diagnosis. 4 Aetiology of chest pain may show considerable variability based on the diagnostic approaches.…”
mentioning
confidence: 99%
“…The coronary artery took a caudal course below the right ventricular outflow tract. In the absence of signs of myocardial ischemia and since the episodes of chest pain had the characteristics of idiopathic chest pain [6] we decided to monitor the patient in the first decade without invasive diagnosis. When she was referred again at the age of 12 years she still had short episodes of chest pain but otherwise she was asymptomatic.…”
Section: Case Presentationmentioning
confidence: 99%
“…Furthermore the CT-scan revealed that the anomalous left coronary artery had neither a slit like opening nor an acute angle of take-off from the aorta which have been identified as possible risk factors for myocardial ischemia in patients with interarterial course [7]. Since the episodes of chest pain had the characteristics of idiopathic chest pain [6] and since prophylactic surgery appeared not justified in the absence of documented ischemia we opted for a conservative approach without restriction of exercise or sports activities and recommended annual follow-up visits [2]. During a follow-up of 2 years the patient remained asymptomatic.…”
Section: Case Presentationmentioning
confidence: 99%
“…On the other hand, chest pain is one of the main causes of recurrent referral to pediatric emergency and pediatric cardiology departments and the most common etiology is still unknown and called as'idiopathic' with a percentage of 21-59 % [12]. Different studies were made to enlight this unknown etiology to this date [13][14][15][16]. However, there has been no published studies that evaluated the relationship between idiopathic chest pain and nutritional deficiencies according to our knowledge.…”
mentioning
confidence: 99%